Reduced Efficiency Roll‐Off and Improved Stability of Mixed 2D/3D Perovskite Light Emitting Diodes by Balancing Charge Injection. (19th July 2019) - Fakharuddin, Azhar; Qiu, Weiming; Croes, Guillaume; Devižis, Andrius; Gegevičius, Rokas; Vakhnin, Alexander; Rolin, Cedric; Genoe, Jan; Gehlhaar, Robert; Kadashchuk, Andrey; Gulbinas, Vidmantas; Heremans, Paul
Abstract: Perovskite light emitting diodes (PeLEDs) have reached external quantum efficiencies (EQEs) over 21%. Their EQE, however, drops at increasing current densities ( J ) and their lifetime is still limited to just a few hours. The mechanisms leading to EQE roll‐off and device instability require thorough investigation. Here, improvement in EQE, EQE roll‐off, and lifetime of PeLEDs is demonstrated by tuning the balance of electron/hole transport into a mixed 2D/3D perovskite emissive layer. The mixed 2D/3D perovskite layer induces exciton confinement and beneficially influences the electron/hole distribution inside the perovskite layer. By tuning the electron injection to match the hole injection in such active layer, a nearly flat EQE for J = 0.1–200 mA cm −2, a reduced EQE roll‐off until J = 250 mA cm −2, and a half‐lifetime of ≈47 h at J = 10 mA cm −2 is reached. A model is also proposed to explain these improvements that account for the spatial electron/hole distributions. Abstract : Improvement in external quantum efficiency (EQE), EQE roll‐off, and lifetime of perovskite light emitting diodes is demonstrated by balancing electron and hole transport/injection into the perovskite emissive layer and perovskite compositional engineering. Charge injection balance together with optimized 2D/3D perovskite stoichiometry leads to nearly flat EQE over a wide current range and lifetime of several tens of hours under continuous operation.